Organisational and Technological Aspects of Usage of Communities of Practice in Tacit Knowledge Management and Organisational Learning - Olszak, M. Celina; Ziemba, Ewa (Advanced Information Technologies for Management – AITM 2008, 2008)
The paper aims at presenting the specifics of communities of practice (CoPs) and the CoPs' role in tacit knowledge and organisational processes management. To meet the above objective, the nature of CoPs is firstly presented. Then, importance of knowledge and organisational learning for the organisation in question is addressed. The most important functions of CoPs in contemporary organisation along with implementation determinants are discussed as well. Finally, a list of selected information tools that allow for effective functioning of CoPs in the aspect of creating tacit knowledge and supporting group work is compiled.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 35, s. 134-149